The influence of neogene lithology on the Šventoji river hydrologic regime - Litvinaitis, Andrius; Bagdžiūnaitė-Litvinaitienė, Lina; Šaučiūnas, Laurynas (International Conference “Environmental Engineering”, 2017)
Due to the recently increasing frequency of extreme changes in river runoff regime, scientific literature deals with the characteristics of runoff formation. Works are carried out in analyzing climate changes and a lot of attention falls on land use structures. Following thorough analysis of the lithological structure of river basins in separate costal zones, this article aims at evaluating river runoff formation characteristics. The basin lithological factor (sandy, loamy, argillaceous) was calculated based on Quaternary map of Lithuania M 1:200000 and Lithuanian river map M 1:50000 using ArcGis software. In order to carry out more thorough analysis of the influence of lithology in given territories, sections of 0–20 m, 50–200 m, 200–500 m, 500–800 m, 800–1000 m and >1000 m were established, calculating the distance in meters from the riverbank. The period of the years 1984–2014 was analyzed, years with the greatest, average and lowest amounts of precipitation (according to probability) was analysed and relation between the runoff and precipitation was established as well as that with the lithological structure, established following a derivation of a hydromodule.
Keywords: lithology; river runoff; precipitation; basin